Indonesia's ambiguous elections : implications for the region - Yang Razali Kassim (2014)
As Indonesians mull over unofficial results of the 9 April legislative elections, two known unknowns remain. In fact, curiosity about the leading presidential contender is growing, despite unofficial results in his favour: Does Joko Widodo (‘Jokowi’) have what it takes to be president?